Regenerative Reading of Heritage in Contemporary Islamic thought – A typical analytical reading of the status of heritage and the objectives of its revival at Mohammed Amara – - azouz, yakoub (Journal of Social Sciences and Humanities, 2023)
Heritage; this term which occupied the Islamic thought, modern and contemporary in particular, is undoubtedly one of the largest and most important issues of interest to thinkers of different position. It has occupied an important place in the discourses of contemporary Islamic thought, especially in light of obsession of modernity and renewal speeches that have become the essence of the renaissance discourse, which tended to pay attention to the reading of heritage, a new reading compatible with the requirements of current life, especially as the issue of heritage has to do with the civilization in light of the increasing challenges of globalization and their overlapping secretion. In the midst of these facts, which require an innovative speech directed towards re-reading the Islamic cultural heritage, the reading of contemporary Islamic thinker Mohammed Amara, who calls for activating the Islamic civilization heritage, re-read and understand its various stations, because of the value and inspirational status of civilization can be guided for construction the new civilization, taking lessons from the experiences of the ancestor of the nation in the addressing the downsides and issues of their time.